2019
DOI: 10.1038/s41436-018-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Introducing medical genetics services in Ethiopia using the MiGene Family History App

Abstract: Medical genetics services are needed in Ethiopia. As other countries increase their genetics capacity, the MFHA can provide fundamental genetics services and collect necessary epidemiologic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…One DHT study reported on genomics data. 89 A psychiatric genomics consortium has made an exchange of data between research groups for genome-wide association studies on neurogenetics of schizophrenia, with tens of thousands of patients and controls included. The consortium developed and used the MiGene Family History App (MFHA) to assist clinicians with the collection and analysis of patient genetic data over six months and assessed its feasibility through a survey of 47 clinicians ( Table 5 ).…”
Section: Digital Health Technologiesmentioning
confidence: 99%
“…One DHT study reported on genomics data. 89 A psychiatric genomics consortium has made an exchange of data between research groups for genome-wide association studies on neurogenetics of schizophrenia, with tens of thousands of patients and controls included. The consortium developed and used the MiGene Family History App (MFHA) to assist clinicians with the collection and analysis of patient genetic data over six months and assessed its feasibility through a survey of 47 clinicians ( Table 5 ).…”
Section: Digital Health Technologiesmentioning
confidence: 99%
“…Currently there are no established medical genetics services with no in-country clinical geneticists or genetic counselors. Previous work though has shown Ethiopian patients are interested in diagnostic and preventative prenatal services with healthcare providers expressing a need for further training in medical genetics and genetic counseling [16,17]. Limited clinical genetic testing consisting of multiplex ligation probe amplification is available through a private lab in Ethiopia since 2014 with plans for platform expansion in the future to include next-generation sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…While the capacity to diagnose congenital anomalies and genetic disease increases at SPHMMC and throughout Ethiopia, only a minority of physicians feel their medical genetics knowledge is sufficient for their practice and the majority are interested in additional genetics education (Quinonez et al., 2019). Prior work at SPHMMC found that 64% of providers reported being asked about congenital disorders/genetic disease multiple times per month, while only 8% stated they were never asked about this by patients/families (Quinonez et al., 2019). While future training of healthcare providers in genetic counseling is planned, Ethiopian patients have no experience with genetic counseling and their attitudes toward genetic counseling warrant consideration prior to training initiation.…”
Section: Introductionmentioning
confidence: 99%